MicroRNAs affecting the susceptibility of melanoma cells to CD8+ T cell‐mediated cytolysis. Issue 2 (30th January 2023) - Pane, Antonino A.; Kordaß, Theresa; Hotz‐Wagenblatt, Agnes; Dickes, Elke; Kopp‐Schneider, Annette; Will, Rainer; Seliger, Barbara; Osen, Wolfram; Eichmüller, Stefan B.
Abstract: Background: The regulatory functions of microRNAs (miRNAs) in anti‐tumour immunity have been mainly described in immune effector cells. Since little is known about miRNA effects on the susceptibility of target cells during T cell—target cell interaction, this study focused on the identification of miRNAs expressed in tumour cells controlling their susceptibility to CD8 + T cell‐mediated cytotoxicity. Methods: Luciferase expressing B16F10 melanoma (B16F10 Luci + ) cells transfected with individual miRNAs covering a comprehensive murine miRNA library were screened for their susceptibility to lysis by an established cytotoxic T lymphocyte (CTL) line (5a, clone Nβ) specific for the melanoma‐associated antigen tyrosinase‐related protein 2. miRNAs with the most pronounced effects on T cell‐mediated lysis were validated and stably expressed in B16F10 cells. In silico analyses identified common targets of miRNA sets determined by the screen, which were further confirmed by small interfering RNA (siRNA)‐mediated silencing experiments modulating immune surveillance. The Ingenuity Pathway Analysis (IPA) software and RNA sequencing (RNA‐seq) data from miRNA‐overexpressing cell lines were applied to investigate the underlying mechanisms. The Cancer Genome Atlas (TCGA)‐derived miRNA sequencing data were used to assess the correlation of miRNA expression with melanoma patients' survival. Results: The miRNA screen resulted in the selection of seven miRNAs enhancing CTL‐mediated melanoma cell killing in vitro. Upon stable overexpression of selected miRNAs, hsa‐miR‐320a‐3p, mmu‐miR‐7037‐5p and mmu‐miR‐666‐3p were determined as most effective in enhancing susceptibility to CTL lysis. In silico analyses and subsequent siRNA‐mediated silencing experiments identified Psmc3 and Ndufa1 as common miRNA targets possibly involved in the functional effects observed. The analyses of RNA‐seq data with IPA showed pathways, networks, biological functions and key molecules potentially involved in the miRNA‐mediated functional effects. Finally, based on TCGA data analysis, a positive correlation of the conserved miRNAs among the panel of the seven identified miRNAs with overall survival of melanoma patients was determined. Conclusions: For the first time, this study uncovered miRNA species that affect the susceptibility of melanoma cells to T cell‐mediated killing. These miRNAs might represent attractive candidates for novel therapy approaches against melanoma and other tumour entities. Abstract : – miRNAs that significantly increase susceptibility of melanoma cells to CTL lysis were discovered. – RNA‐seq analyses show networks and pathways potentially involved in enhanced susceptibility to CTLs. – TCGA data analyses reveled correlations between expression of certain newly identified miRNAs and patient survival. – These miRNAs might promote the development of novel cancer therapies.